Strengthening Sustainable Competitive Advantage Through Green Innovation And Social Capital: Evidence From Coastal Small Medium Enterprises - Arie Frits Kawulur; Tinneke Evie Meggy Sumual; Hisky Ryan Kawuur (Journal of The Community Development in Asia, 2026)
This study investigates the how social capital and green innovation interact to strengthen sustainable competitive advantage among coastal small and medium enterprises (SMEs) in Indonesia. Data were collected from 78 coastal small medium enterprise through a structured survey and analyzed using partial least squares structural equation modeling. The results reveal that social capital has a significant positive impact on both green innovation and sustainable competitive advantage. Furthermore, green innovation became a crucial factor in strengthening sustainable competitive advantage, indicating the adoption of eco innovative practices can improve firms’ environmental and market performance. The findings underscore the strategic importance of integrating social and environmental dimensions to achieve long term competitiveness in resource constrained regions. Theoretically, the study extends sustainability literature by conceptualizing social capital as a dynamic capability that drives innovation based advantage. Practically, it provides insights for managers and policymakers to foster collaborative ecosystems and incentive mechanisms that promote green innovation and environmental stewardship among coastal regions.